Shock Index in the early assessment of febrile children at the emergency department: a prospective multicentre study. Issue 2 (22nd June 2021) - Hagedoorn, Nienke N; Zachariasse, Joany M; Borensztajn, Dorine; Adriaansens, Elise; von Both, Ulrich; Carrol, Enitan D; Eleftheriou, Irini; Emonts, Marieke; van der Flier, Michiel; de Groot, Ronald; Herberg, Jethro Adam; Kohlmaier, Benno; et al.
Abstract : Objective: (1) To derive reference values for the Shock Index (heart rate/systolic blood pressure) based on a large emergency department (ED) population of febrile children and (2) to determine the diagnostic value of the Shock Index for serious illness in febrile children. Design/setting: Observational study in 11 European EDs (2017–2018). Patients: Febrile children with measured blood pressure. Main outcome measures: Serious bacterial infection (SBI), invasive bacterial infection (IBI), immediate life-saving interventions (ILSIs) and intensive care unit (ICU) admission. The association between high Shock Index (>95th centile) and each outcome was determined by logistic regression adjusted for age, sex, referral, comorbidity and temperature. Additionally, we calculated sensitivity, specificity and negative/positive likelihood ratios (LRs). Results: Of 5622 children, 461 (8.2%) had SBI, 46 (0.8%) had IBI, 203 (3.6%) were treated with ILSI and 69 (1.2%) were ICU admitted. High Shock Index was associated with SBI (adjusted OR (aOR) 1.6 (95% CI 1.3 to 1.9)), ILSI (aOR 2.5 (95% CI 2.0 to 2.9)), ICU admission (aOR 2.2 (95% CI 1.4 to 2.9)) but not with IBI (aOR: 1.5 (95% CI 0.6 to 2.4)). For the different outcomes, sensitivity for high Shock Index ranged from 0.10 to 0.15, specificity ranged from 0.95 to 0.95, negative LRs ranged from 0.90 to 0.95 and positive LRs ranged from 1.8 to 2.8. Conclusions: High Shock Index is associated with serious illness in febrile children. However, its rule-out value is insufficient which suggests that the Shock Index is not valuable as a screening tool for all febrile children at the ED. Abstract : EU multicentre ED study of presenting vital signs in >5000 febrile children with an association between "shock index" and serious illness, but low sensitivity limits utility in screening.